2004
DOI: 10.7863/jum.2004.23.6.777
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Safety of Ultrasound‐Guided Fine‐Needle Aspiration of Salivary Gland Masses Including a Cytologist's Review

Abstract: Objective. To evaluate the utility and safety of ultrasound-guided fine-needle aspiration of the salivary glands for diagnosis of focal masses in the salivary glands, including the prevalence of nondiagnostic sampling, the impact of the presence of a cytologist during the procedure, and the usefulness of flow cytometry. Methods. A retrospective analysis of 43 ultrasound-guided fine-needle aspirations of the salivary glands from 36 lesions in 33 patients was performed. Fine-needle aspirations were obtained unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…Many investigators believe that the common practice of FNAC performed by clinicians produces suboptimal results in salivary gland masses. With immediate assessment of the material by a cytopathologist, the combined approach of ultrasound-guided FNAC in salivary gland masses is more accurate than with specimens obtained with other techniques [3,4,21] . In contrast, some investigators believe that training and ability in specimen interpretation are the most important features.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators believe that the common practice of FNAC performed by clinicians produces suboptimal results in salivary gland masses. With immediate assessment of the material by a cytopathologist, the combined approach of ultrasound-guided FNAC in salivary gland masses is more accurate than with specimens obtained with other techniques [3,4,21] . In contrast, some investigators believe that training and ability in specimen interpretation are the most important features.…”
Section: Discussionmentioning
confidence: 99%
“…21 Sonographically guided FNAB is a safe procedure with a low rate of nondiagnostic sampling. 20 In previous studies, the sensitivity of US-guided FNAB for detecting malignant lesions was reported at 82-85% and specificity at 86-96%. 17,19 FNAB is currently regarded as a minimally invasive, accurate, and cost-effective technique in the evaluation of parotid and other salivary gland lesions.…”
Section: Discussionmentioning
confidence: 99%
“…18 FNAB is a well-established tool to diagnose salivary gland lesions. 2,3,16,17,[19][20][21][22][23][24] Although it is generally accepted that FNAB is useful in the preoperative setting, its accuracy is highly dependent on both operator experience and the interpretative skills of the cytopathologist. 21 Sonographically guided FNAB is a safe procedure with a low rate of nondiagnostic sampling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal involvement may also be encountered, with a focal hypoechoic heterogeneous lesion within a normally shaped gland (36,37). In all doubtful cases, verification with fine-needle aspiration biopsy is recommended (38,39).…”
Section: Chronic Sclerosing Sialadenitismentioning
confidence: 99%